2022
DOI: 10.1108/bij-09-2021-0525
|View full text |Cite
|
Sign up to set email alerts
|

Cab-sharing services and transformation expectations of consumers: the moderating role of materialism

Abstract: PurposeThe study examines the role of attitude, perceived relative advantage and perceived risk on intention to participate in the sharing economy–based cab services in India. Further, it investigates the impact of intention to participate in the sharing economy on transformation expectations of consumers. Finally, the study tests the moderating role of materialism in the relationship between intention to participate in the sharing economy and transformation expectations of consumers.Design/methodology/approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 105 publications
2
7
0
Order By: Relevance
“…Customer-customer interactions during sharing economy usage is driven by social value through participation in prosocial activities (Davlembayeva et al, 2020). Previous research has shown that the intention to engage in prosocial behaviours can result in transformation expectations (Davidson et al, 2018;Shaikh et al, 2023). The current study extends the previous research (Feng and Guo, 2017).…”
Section: Theoretical Contributionssupporting
confidence: 68%
See 4 more Smart Citations
“…Customer-customer interactions during sharing economy usage is driven by social value through participation in prosocial activities (Davlembayeva et al, 2020). Previous research has shown that the intention to engage in prosocial behaviours can result in transformation expectations (Davidson et al, 2018;Shaikh et al, 2023). The current study extends the previous research (Feng and Guo, 2017).…”
Section: Theoretical Contributionssupporting
confidence: 68%
“…philanthropic giving) can result in self-transformation through better sense of self Evren and Minardi (2017) Prosocial actions (e.g. donations) can result in a "warm glow" for the donors Relational transformation expectations Stieler and Germelmann (2016) Customer-customer exchanges can result in in-group belongingness and foster connectedness among group members Shaikh et al (2023) Participation in sharing economy in Indian context creates sense of belonging and shared social identity for customers Well-being Tang and Blocker (2022) Interactions among members of disadvantaged social groups can help ensure collective well-being Feng and Guo (2017) Altruistic and prosocial behaviours can promote selfesteem and drive well-being Source(s): Created by author , 2015). When customers participate to co-create value for other customers in technology-based online services, they can shape other customers' decisions and offer informational and emotional support (Nadeem et al, 2020;Torkzadeh et al, 2021).…”
Section: Customer (Lender) Participation and Financial Empowerment Of...mentioning
confidence: 99%
See 3 more Smart Citations